Kandungan Nutrien (Nitrat dan Fosfat) di Sungai Seruai, Sumatera Utara - Bryan Baginta Gurusinga; Ima Yudha Perwira; Alfi Hermawati Waskitasari (Current Trends in Aquatic Science, 2022)
Seruai River is a river located in the administrative area of ??Deli Serdang Regency, North Sumatra. The Seruai River has the potential to influence the increase in nutrient content in the watershed, because there are many interactions between land and water that cause changes in nutrient content in the Seruai River. The study was carried out during July 2021. The analysis used a descriptive method and used Indonesian Government Regulation Number 22 of 2021 as a comparison of water quality. Determination of sample points using purposive sampling method. The water parameters measured in this study were nitrate, phosphate, DO, pH, temperature and TDS. Based on the results of the study showed that there was an increase in the content of nitrate and phosphate content from upstream to downstream. The nitrate content from upstream to downstream ranged from 5.5 mg/L to 16.9 mg/L, while the phosphate content from upstream to downstream ranged from 0.2 mg/L to 1.8 mg/L. The rate of increase in nitrate upstream to the middle is 0.026 mg/L.km while the middle to downstream is 0.123 mg/L.km. The rate of increase in phosphate from upstream to midstream is 0.005 mg/L.km while the middle to downstream is 0.010 mg/L.km. The highest nitrate and phosphate content was in the sampling week 04/07/2021 while the lowest nitrate content was in the 25/07/2021 week and the lowest phosphate was in the sampling week 18/07/2021.